Comparison and selection of coagulants between Moringa Oleifera dan aluminium sulfate (alum) - Lim Bee Sian (School of Environmental Engineering , University Malaysia Perlis, 2011)
This study was designed to investigate the efficiency of using two coagulants that is natural coagulant and chemical coagulant in Methylene Blue colour removal. In the study of the Natural Coagulant that is M.O., the most effective of the coagulant are 5 % M.O. in 100 ml NaCl that is achieve 56 % removal rate in 100 mg/L Methylene Blue. The study shows that the colour removal of M.O in different extraction method. For extraction with distilled water, the highest removal efficiency is 10 % in dosage 80 ml of M.O.. For extraction of M.O with NaCl the highest efficiency is 70 % in dosage 80 ml. From the result we can see that the extractions of M.O. with NaCl are 7 times higher than extraction of M.O. with distilled water. For Chemical Coagulant, it show in 5 % ALUM as coagulant in Methylene Blue the lower colour removal efficiency for ALUM is 20 % in 20 ml for pH 7 and the higher removal efficiency for ALUM is 23 % in 100 ml for pH 9. Besides high efficiency of dye removal, the natural coagulant treatment process offers many advantages for potential application such as coagulant savings, minimal amount of sludge formation and also good for environment and health effect.